A proposed scenario for amending the secondary education system in Palestine; In light of the standardization of the occupational preference scale - Arar, Rashid Mohammed; Abdullah, Tayseer Mohammed (Journal of Educational and Psychological Sciences, 2020)
The study aimed to present a proposed concept for amending the secondary education system in Palestine, in light of standardization the scale of vocational inclinations, according to the variables of gender and the level of academic achievement, on a sample of (1478) students, chosen in a cluster manner, and then stratified from all the class students. The results indicated the achievement of the global construction of the occupational inclinometer, with good indications of validity and good reliability, through the validity of the hypothetical composition, internal consistency, discriminatory validity, alpha reliability, reapplication, and exploratory factor analysis. That showed the presence of eight factors that accounted for 76% of the total variance. The division of secondary education into three tracks: the scientific track: it includes: (the health, industrial, agricultural, and technological branch). The literary track includes: (Branch of Humanities, Sharia, Entrepreneurship and Business). The applied path includes: (the hotel branch, the beauty, the fashion branch and the customization of clothes). This division will contribute to modifying the inferior view of vocational education on the one hand, increasing the demand for professional branches on the other hand, and reducing dropout rates, as well as reducing the suffering and anxiety of parents. The study recommended the issuance of the second Education Law; to include an amendment of the secondary education system, and the approval of the results of the vocational inclinometer as a criterion besides academic achievement; to distribute students to the tenth grade (scientific, literary, and applied) branches as a prelude to distributing them to high school branches.